Principal Instructional Leadership in the Implementation of the "Wednesday Literacy Movement" to Improve Student Literacy and Numeracy Achievement - Lusia Widiastuti; Saryanto Saryanto; Jumintono Jumintono (Journal of Creative Power and Ambition (JCPA), 2026)
Improving the quality of basic education in the current era of educational transformation is closely linked to schools' ability to build a strong learning culture, particularly in literacy and numeracy. This article aims to analyze the principal's instructional leadership in the implementation of the Wednesday Literacy Movement to improve student literacy and numeracy outcomes at SD Negeri 2 Jengkol. The study used a qualitative approach with a case study type. The research subjects included the principal, teachers, and students involved in the program implementation. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the principal's instructional leadership plays a significant role in the successful implementation of the Wednesday Literacy Movement through three main aspects, namely planning, implementation, and evaluation. In the planning stage, the principal establishes the program vision, involves teachers, maps needs, and integrates literacy and numeracy into school activities. In the evaluation stage, the principal monitors, reflects with teachers, assesses student progress, and follows up on the program based on the evaluation results. The research findings confirm that the principal's instructional leadership functions not only as program management but also as a learning strategy capable of encouraging improved student literacy and numeracy skills through directed, collaborative, and sustainable learning habits.